Optical Frequency Comb Generation Based on Optoelectronic Oscillator and Fabry-Perot Phase Modulator - Kunpeng Zhai; Wenting Wang; Sha Zhu; Huashun Wen; Ninghua Zhu (IEEE Photonics Journal)
We propose and demonstrate an optical pulse generator using optoelectronic oscillator (OEO) and Fabry-Perot phase modulator (FP-PM). A complete theoretical analysis is developed, and the advantages of the proposed system are also discussed. The optical frequency comb (OFC) is generated with an OEO loop to create broadband comb mode with low noise. It is theoretically proved that OFC pulses with a spectrum of 33 flat comb lines can be generated using an FP-PM. 25 GHz optical pulses with full-width-at-half-maximum (FWHM) less than 4 ps, signal-to-noise ratio (SNR) better than 40 dB. By changing the length of the fiber in OEO, the timing jitter is 100 fs in this system. The phase noise of the 25 GHz signal is −107.8 dBc/Hz at 10 kHz offset, which is measured when the fiber length is 230 m. The system is promising to attain high-quality electrical-optical (EO) comb with low timing jitter.